Prevalence and comparison of high-level aminoglycoside resistance in vancomycin-sensitive and vancomycin resistant enterococcus at a tertiary care hospital in Rohillkhand region - Deepika verma; Shivani sinha; Ved Prakash (International Journal of Medical Research and Review, 2015)
Introduction: Enterococci, originally commensals of gastrointestinal tract, have now become important nosocomial pathogens. The serious infections caused by Enterococci were empirically treated with bactericidal combination of beta lactam drugs and aminoglycoside neither of which are effective alone [1]. But the presence of high level aminoglycoside resistance (HLAR) makes this treatment ineffective. The emergence of VRE (Vancomycin Resistant Enterococcus) strains also resistant to ampicillin and HLAR has made the treatment further difficult. The spread of such strains in a health care environment has to be constrained and so the present study was carried out to highlight the occurrence of HLAR strains and VRE strains in our hospital .The frequency of association of HLAR with VSE (Vancomycin sensitive Enterococci) and VRE (Vancomycin resistant Enterococci) and any significant difference between the two was also studied.Methods: A total of 100 Enterococci were isolated from 6272 clinical specimen during a study period of 1 year. These strains were speciated on the basis of biochemical tests. Antimicrobial susceptibility test was performed by Kirby baeur disc diffusion method. High level Aminoglycoside resistance was tested by two methods 1) 150μg gentamicin and 200 μg streptomycin disc 2) Agar screening method. Similarly, strains resistant to Vancomycin by disc diffusion method were subjected to confirmatory test by determining their MIC by Agar dilution.Results: A total of 100 Enterococci were isolated during a study period of one year. The prevalence of HLAR was found to be 49%.The prevalence of VRE was found to be 12%.VRE strains also possessing resistance to High strength Gentamycin and or streptomycin was 8%.The frequency of association of HLAR in VRE was 1.5 times higher as compared to VSE.Conclusion: The prevalence of High level gentamicin and high level streptomycin resistance amongst Enterococcal isolates in our institute was high. More enterococcal strains were found to be resistant to both gentamicin and streptomycin than to gentamicin or streptomycin alone. The HLAR rate in VRE was 1.5 times higher than in VSE.